Nutritional plans on the intake, digestibility, and performance of dairy heifers of different breed compositions - Oliveira Filho, Carlos Alberto Alves; Machado, Fernanda Samarini; Ferreira, Alexandre Lima; Tomich, Thierry Ribeiro; Maurício, Rogério Martins; Campos, Mariana Magalhães; Silva, Camilla Flávia Portela Gomes da; Azevêdo, José Augusto Gomes de; Pereira, Luiz Gustavo Ribeiro (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to evaluate the effects of nutritional plans and breed composition on nutrient intake and digestibility, nitrogen balance, and performance of dairy heifers in tropical conditions. Thirty-six heifers – 12 Holstein, 12 Gyr, and 12 Gyrolando F1 (½ Holstein × ½ Gyr) – were housed in a tie-stall system and randomly distributed, adopting a completely randomized design in a 3×3 factorial arrangement (nutritional plans and breed composition). The diets were formulated to enable weight gains of 200, 400, and 800 g per day, corresponding to the nutritional plans 11, 14, and 19 g kg-1 body weight (BW), respectively. The intake of dry matter, fibrous fractions (g kg-1 BW-0.75), and metabolizable energy (kcal-1 BW-0.75) in the 11-g kg-1 plan were greater for Gyr heifers than for Gyrolando and Holstein heifers. Ether extract digestibility was 13.85% higher for Gyr heifers compared with Gyrolando F1 in the 19-g kg-1 plan. The increase in the nutritional plans shows a quadratic response to nutrient intake and a linear response to average daily gain, but does not affect the digestibility coefficients. Gyr and Gyrolando F1 heifers present similar nutritional efficiency to that of Holstein heifers.